PENGENDALIAN INTERNAL DALAM MANAJEMEN PERSEDIAAN : (Studi Kasus pada PT Rajawali Hiyoto Cabang Malang) - Retno Murni Sari; Rumanintya Lisaria Putri (Fakultas Ekonomi Universitas 45 Surabaya, 2015)
Inventories of finished goods is one that affects the current assets of the company. To avoid things that could hurt the company, the necessary internal controls in the management of inventory until the distribution to the consumer. The purpose of this study was to menganlisis and determine the application of internal controls in the management of inventories of finished goods to the distribution process at PT Rajawali Hiyoto Malang branch. This research uses qualitative data with the inductive approach. From the results of research at PT Rajawali Hiyoto Branch Malang, implementation of internal controls in the management of inventories of finished goods to the distribution process still needs to be improved. It can be proved by the lack of delivery fleet, part of the income and expenditure of goods in warehouses Surabaya done by men are the same warehouse and inventory damaged / worn out in the barn. But the procedures relating to the inventory done quite well. It can be proved by evidence of any tranksaksi tranksaksi like when expenditure and receipt of inventory.